Evaluation of the Preventive Efficacy and Safety of Azoximer Bromide in Healthcare Workers in Contact with Patients Hospitalized for COVID-19 - K V Kasyanenko; O V Maltsev; K V Kozlov; K V Zhdanov; A A Kuzin; A E Zobov; A V Puzikov (Эпидемиология и вакцинопрофилактика)
Relevance. Despite the implementation of measures to reduce morbidity and mortality among medical workers who are in contact with patients hospitalized for a new coronavirus infection caused by SARS-CoV-2 (hereinafter – COVID-19), their level remains high today. Given the difficulty of achieving the required number of vaccinated to form collective immunity, the issue of finding additional drug-based ways to prevent COVID-19, especially in risk groups, becomes urgent. Aims. To evaluate the effect of azoximer bromide on the number of cases of confirmed COVID-19 disease among medical workers, as well as on the level of chronic fatigue in the study groups. Materials and methods: 78 men and women were included in the study. The experimental group consisted of 41 people who took azoximer bromide for 38 days. The comparison group consisted of 37 people who were not prescribed azoximer bromide. The epidemiological efficacy of the drug was evaluated. Statistical evaluation of the significance of the differences was carried out using the Student's t-test, Pearson's criterion χ2. Results. The number of study participants with COVID-19 in the experimental group was significantly lower than in the comparison group. A significantly faster reduction of manifestations of chronic fatigue syndrome was noted in study participants who took azoximer bromide. There were no adverse events during the administration of the studied drug by the study participants. Conclusions. Azoximer bromide has shown epidemiological efficacy when used by medical workers directly providing medical care to patients with COVID-19 (when working in the «red zone»), including contributing to the more rapid normalization of the psychological state of medical workers